Perceived Herding Behavior and Experienced Regret on Crypto Asset’s Investment Decisions by Millennials - Rosmiwilujeng, Elyza Putri; Made Dudy Satyawan; Paino, Halil (AKRUAL: Jurnal Akuntansi, 2024)
ntroduction/Main Objectives: This research aims to determine the effect of herding behaviour and experienced regret on millennials’ decisions to invest in crypto assets. In addition, this research would explain the investment decisions of crypto assets in urban communities in the Surabaya and Sidoarjo areas. Background Problems: The number of crypto asset enthusiasts had increased significantly over the past few years. Commodity Futures Trading Supervisory Agency (Badan Pengawas Perdagangan Berjangka Komoditi/BAPPEBTI) noted that crypto investors in Indonesia had reached 17.25 million people in April 2023. Under these conditions, investors’ behaviour can be influenced by psychological and emotional factors such as herding behaviour and experienced regret. Research Methods: The research method used a survey method with a sample of students and employees domiciled in the urban areas of Surabaya and Sidoarjo. The analysis technique used in this research was multiple linear regression analysis using SPSS version 26 software. Finding/Results: The research results showed that herding behaviour and experienced regret had a partially positive effected on millennials’ investment decisions in crypto assets. Conclusion: The novelty of this research was to explain the differences in crypto asset investment decisions between students and employees